COMPARATIVE EVALUATION OF THE EFFECTIVENESS OF ABICTIN AND ALBENDAZOLE IN SHEEP MONIESIOSIS - Гусманов, М. Г.; Абирова, И. М.; Абирова, Н. А. (Ғылым және білім=Наука и образование=Science and education № 1-1(66), 2022)
The total number of sheep in the Republic of Kazakhstan, according to the Statistics Committee, is 16.399 million heads, including 955974 heads in the West Kazakhstan region, 11.7% of the total livestock. Crossbred sheep breeding is developing in the West Kazakhstan region. The article discusses a comparative assessment of the effectiveness of the use of abectin and albendazole in sheep moniesiosis. The development of sheep breeding is hindered by many factors, such as the imperfection of the feeding system, production, management methods, etc. One of the most common reasons that do not allow to fully realize all the possibilities of this industry is a parasitic infection. According to the norms of the World Health Organization, the consumption of lamb meat per year by one person should be 18.2 g. However, there are many reasons that interfere with sheep farming on farms, as well as reducing the quality of meat. These include diseases of sheep, in particular monesiosis. The distribution and causes of the foci of moniesiosis in the West Kazakhstan region have been studied. Based on the methods of veterinary and sanitary examination, the safety of drugs for the consumer has been confirmed, but at the same time the nutritional value of the meat of an animal with moniesiosis is reduced. Based on the analysis and generalization of experimental data, their testing in production conditions, it was determined that the drug "Abictin injection" at a dose of 1 ml / 50 kg (0.2 ml / kg) of body weight, has a pronounced anthelmintic effect on the cestode of the genus Moniezia.Общая численность овец в Республике Казахстан, по данным Комитета статистики, составляет 16,399 млн. голов, в том числе в Западно-Казахстанской области – 955974 головы 11,7% от общего поголовья. В Западно-Казахстанской области развивается кроссбредное овцеводство. В статье рассматривается сравнительная оценка эффективности применения абектина и альбендазола при мониезиозе овец. Развитию овцеводства препятствуют многие факторы, такие как несовершенство системы кормления, производства, методов управления и т.д. Одна из наиболее распространенных причин, не позволяющих в полной мере реализовать все возможности этой отрасли, – паразитарная инфекция. По нормам Всемирной организации здравоохранения, потребление мясо баранины в год одним человеком должно составлять 18,2 г. Однако существуют много причин мешающих овцеводству в хозяйствах, а также снижающих качество мяса. К таким относятся болезни овец, в частности мониезиоз. Изучены распространение и причины возникновения очагов мониезиоза в Западно-Казахстанской области. На основании проведенных методов ветеринарно-санитарной экспертизы подтверждена безопасность препаратов для потребителя, но при этом пищевая ценность мяса животного, больного мониезиозом снижается. На основании анализа и обобщения экспериментальных данных, апробации их в производственных условиях определено, что препарат «Абиктин иньекционный» в дозе 1мл/50кг(0,2 мл/кг) массы тела, оказывает выраженное антигельминтное действие на цестод рода Moniezia.
Keywords: научный журнал; отечественное издание; периодическое издание; журнал коксон; ветеринария; болезни овец; мониезиоз овец; паразитарная инфекция; Sheep; moniesiosis